In an antique land - Ghosh, Amitav (New Delhi Ravi Dayal, 2000)
In an Antique land is subversive history of a travellers tale.It provides magical and intimate insights in to Egypt from the crusades to operation Desert strom.It also offers of the many small indistinguishable and intertwining histories of India and Egyp
Keywords: Africa-Description and travel; Africa-Geography and Maps